Pricing and procurement strategies in the relief supply chain via bidirectional option contract - Mahsa Maleki Rastaghi; Farnaz Barzinpour; Jafar Heydari; Mohammad Reza Gholamian (PLoS ONE, 2026)
Humanitarian supply chain management is a critical and challenging issue for all members of the supply chain due to the high uncertainty of the demand caused by a disaster and the direct connection of this type of supply chain with the well-being of the affected individuals. One strategy to increase supply flexibility and reduce the risk of inventory shortages or surpluses in humanitarian supply chains is to use option contracts. In this study, we investigate the optimization of decisions in a two-echelon humanitarian supply chain consisting of a humanitarian organization and a supplier through a bidirectional option contract, considering the perspectives of both supply chain members. We rely on realistic assumptions regarding the relief supply chains, such as the occurrence probability of disasters and differing salvage values of the supplier and the humanitarian organization. In addition, the optimal decisions of the humanitarian organization and supplier are extracted based on the Stackelberg game. Then, we demonstrate that when the humanitarian organization’s salvage value is equal to the supplier’s, the bidirectional option contract becomes a call option contract. Under the same condition, optimal procurement and pricing strategies of the humanitarian organization and the supplier are extracted. Finally, we show through numerical examples that the performance of the proposed model more closely resembles that of the centralized model than the wholesale price model in improving the supply chain members’ objectives. The results indicate that using a bidirectional option contract leads to improvements in supply chain members’ performance and can help achieve channel coordination.